Fully covered metallic stents in biliary stenosis after orthotopic liver transplantation - Tarantino, I.; Traina, M.; Mocciaro, F.; Barresi, L.; Curcio, G.; Di Pisa, M.; Granata, A.; Volpes, R.; Gridelli, B. (Endoscopy, 2012)
Background and study aims: Data from a preliminary study suggested that the placement of a fully covered metal stent may be a valid alternative to surgery in patients who do not respond to standard endoscopic treatment. The aims of the current study were to evaluate the clinical success of self-expandable metallic stents (SEMS) in a large cohort of patients and with a long follow-up, and the effectiveness of SEMS placement as a first-line procedure.Materials and methods: Between January 2008 and August 2010, 54 consecutive patients with biliary complications following orthotopic liver transplantation were treated with SEMS placement: 39 after failure of conventional endoscopic therapy (Group I), and 15 with no previous endoscopic treatment who were undergoing SEMS placement as first-line treatment for complications (Group II).Results: In Group I, resolution after SEMS removal was observed in 71.8 % of patients. Mean follow-up after resolution was 22.1 ±10 months. Recurrence of the complication was observed in 14.3 % of patients after a mean of 8.5 months and SEMS migration was observed in 33.3 % of patients. In Group II, resolution was observed in 53.3 % of patients. Mean follow-up after resolution was 14.4 ±2.2 months. Recurrence was observed in 25 % of patients and SEMS migration was observed in 46.7 %.Conclusions: For endotherapy of biliary complications after orthotopic liver transplantation, metallic stents should not be used as the primary modality. In patients in whom the standard approach fails, treatment with temporary SEMS placement can solve biliary complications in almost three-quarters of cases; however stent migration (33 %) remains a problem.